Calendar Anomalies in African Stock Markets: Does the Effect of Covid-19 Pandemic Matter? - Alloul, Fouzia; Ferrouhi, El Mehdi (Organizations and Markets in Emerging Economies, 2025)
The Covid-19 pandemic profoundly disrupted global economies and financial systems, altering investor behavior and challenging traditional market dynamics. Among these disruptions, calendar anomalies, which challenge the efficient market hypothesis, offer a unique lens to assess market efficiency during crises. The objective of this study is to examine the impact of Covid-19 on calendar anomalies in the main African stock markets, an area largely overlooked in existing research despite the region’s increasing importance in global financial systems. Using daily closing prices from January 1, 2009 to December 31, 2021, and employing a GJR-GARCH (1,1) model, the findings indicate that calendar anomalies exhibit temporal variation within the sample markets, influenced by trends that shift markets between periods of efficiency and inefficiency. Additionally, the study highlights the emergence of new calendar anomalies coinciding with the onset of the Covid-19 pandemic. These results offer lasting insights for investors, suggesting the need for dynamic trading strategies that can adapt to calendar anomalies during global crises. For policymakers, the research underscores the importance of reducing information asymmetry to enhance market resilience in times of crisis. The study also emphasizes the need for further research to explore how systemic shocks, such as Covid-19, can disrupt traditional market patterns and affect stock market behavior.